35th anniversary retrospective - Polachek, S. W.; Tatsiramos, Konstantinos (Research in labor economics ;, 2012)
Since its inception Research in Labor Economics has published over 350 articles encompassing a wide range of themes and spanning an array of labor economics topics. Authors have ranged from young scholars with much potential to mature leaders in the field, including Nobel Prize and John Bates Clark award winners. Over the years Research in Labor Economics has continued to present important new research in labor economics. It covers themes such as labor supply, work effort, schooling, on-the-job training, earnings distribution, discrimination, migration, and the effects of government policies on worker well-being. It aims to apply economic theory and econometrics to analyze important policy-related questions, often with an international focus. To commemorate Research in Labor Economics's 35th anniversary, this retrospective edition contains 20 of the most influential Research in Labor Economics articles along with new introductory prefatory updates written by the original authors. These new prefaces emphasize recent developments that each article might have inspired and also discuss remaining unanswered questions.